(untitled) (Baghdad Science Journal, 2025)
Pseudomonas aeruginosa is a common and major opportunistic human pathogen, its causes many and dangersinfectious diseases due to death in some timesex: cystic fibrosis , wounds inflammation , burns inflammation , urinary tract infection , other many infections otitis external , Endocarditis , nosocomial infection and also causes other blood infections (Bacteremia). thereforebecomes founding fast and exact identification of P. aeruginosafrom samples culture very important.However, identification of this species may be problematic due to the marked phenotypic variabilitydemonstrated by samples isolates and the presence of other closely related species. To facilitate species identification, we used 16S ribosomal DNA(rRNA) sequence data toidentify genus- and species-specific 16S rRNA signature sequences,its account a stable part of the geneticcode. Based on these sequences we designed simple, rapid, and accurate PCR assays that allow the differentiation of P. aeruginosa from Pseudomonas species and other pathogen genus ,also this test considered as the most specific than the other diagnostic tests like API (20) which give 70% while the 16SrRNA test give more than 90 %.